If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 18 = 3 Reorder the terms: 18 + -5x = 3 Solving 18 + -5x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -5x = 3 + -18 Combine like terms: 18 + -18 = 0 0 + -5x = 3 + -18 -5x = 3 + -18 Combine like terms: 3 + -18 = -15 -5x = -15 Divide each side by '-5'. x = 3 Simplifying x = 3
| 2x+3-5x-2= | | 6x+2=2x+24 | | 3x-1.2=-4.8 | | -3(2d-6)=6(-d-5) | | ln(2x)=16 | | 3y=4x+8 | | 4z+2(z-4)=3z+11 | | 4-(-13.5)= | | 3y=4c+8 | | x^2=-3x+54 | | (x-5)(7+x)=0 | | y=120+16(12) | | 6-d=-1 | | (x^2+34)+(6x+4)+(10x+10)=180 | | 5m-7=6m+11 | | -3(2c-6)-4(c-3)=20c-20 | | 9(z-8)= | | s=4r^2t | | 2x+1=6x+17 | | 2x^2-11c-40=0 | | 9x^3-90x^2+81x=0 | | (-0.3)*(x-2)=3.6 | | X+x+7+8=25 | | 3j+4y=12j+16 | | i+i+w+w= | | s+s+s+s= | | y=90+14(5) | | -10.82=m | | 4z+4z=7z+8 | | 8x+9y=56 | | Y^2=4(-2y+40)-55 | | -9(z+5)-(-7z-7)=3z |